Arrhythmias in Chronic Kidney Disease - Zaki Akhtar; Lisa WM Leung; Christos Kontogiannis; Isaac Chung; Khalid Bin Waleed; Mark M Gallagher (European Cardiology Review)
Arrhythmias cause disability and an increased risk of premature death in the general population but far more so in patients with renal failure. The association between the cardiac and renal systems is complex and derives in part from common causality of renal and myocardial injury from conditions including hypertension and diabetes. In many cases, there is a causal relationship, with renal dysfunction promoting arrhythmias and arrhythmias exacerbating renal dysfunction. In this review, the authors expand on the challenges faced by cardiologists in treating common and uncommon arrhythmias in patients with renal failure using pharmacological interventions, ablation and cardiac implantable device therapies. They explore the most important interactions between heart rhythm disorders and renal dysfunction while evaluating the ways in which the coexistence of renal dysfunction and cardiac arrhythmia influences the management of both.